Manager's Influence on Subordinates' Thinking About Safety - Dunbar, Roger L. M. (Academy of Management Journal, 1975)
Organizational climate may be an important determinant of the way organization members think about safety. Some organizational climates may tend to encourage subordinates to take individual responsibility for safety matters; others may encourage a belief that safety, like other aspects of organizational effectiveness, is a management responsibility. This paper explores the effects of one aspect of organizational climate on subordinates' thinking about safety.